Odpowiedź :
Odpowiedź:
Przepraszam ale podpunkt r był dla mnie skomplikowany
Odpowiedź:
f) -12 - 11 = × + 19 + 2×
-12 - 11 - 19 =× + 2×
- 42 = 3× /:3
- 14 = ×
g) 2× - × + 6 = -4 + 2×
2× - × - 2× = -4 - 6
-× = -10
× = 10
h) 24 - 6× = 2× - 4× - 12
24 + 12 = 2× - 4× + 6×
36 = 4× /:4
9 = ×
n) 2 • (3× - 2) + 3 • (2× - 2) = 8
6× - 4 + 6× - 6 = 8
6× + 6× = 8 + 4 + 6
12× = 18 /:12
× = 1,5
o) 4× - 3 • (× - 4) = 32
4× - 3× + 12 = 32
4× - 3× = 32 - 12
× = 20
p) -6 • (× + 2) = -4 - 5×
-6× - 12 = -4 - 5×
-6× + 5× = -4 + 12
-× = 8
x = 8
r) -3 • (4× + 2) + 5× = × - (9 - 4×)
-12× - 6 + 5× = -9× - 4×^2
-6 = -9× - 4×^2 + 12×
-6 = -13×^2 + 12×
-6 = -×^2
s) 3 • (× + 4) = 20
3× + 12 = 20
3× = 20 - 12
3× = 8 /:3
× = 2,6
t) 4 • (× + 5) - 8 = 2
4× + 20 - 8 = 2
4× = 2 - 20 + 8
4× = -10 /:4
× = - 2,5
u) 2 • (3a + 7) + a = 70
6a + 14 + a = 70
6a + a = 70 - 14
7a = 56 /:7
a = 8
w) 54 = 2 • ( 3× - 2)
54 = 6× - 4
54 + 4 = 6×
58 = 6× /:6
9,6 = ×
Mam nadzieję że pomogłam :)